A Comparison of Microsatellites in Phytopathogenic Aspergillus Species in Order to Develop Markers for the Assessment of Genetic Diversity among Its Isolates - Mahfooz, Sahil; Singh, Satyendra P.; Mishra, Nishtha; Mishra, Aradhana (Frontiers in Microbiology, 2017)
The occurrence of Microsatellites (SSRs) has been witnessed in most of the fungal genomes however its abundance varies across species. In the present study, we analyzed the frequency of SSRs in the whole genome and transcripts of two phyto-pathogenic (Aspergillus niger and Aspergillus terreus) and compared them with two non-pathogenic (Aspergillus nidulans and Aspergillus oryzae) Aspergillus. Higher relative abundance and relative density of SSRs were observed in the whole genome and transcript sequences of the pathogenic Aspergillus when compared to the non-pathogenic. The relative abundance and density of SSRs were positively correlated with the G+C content of transcripts. Among the different classes of SSR, the percentage of tetra-nucleotide SSRs were maximum in A. niger (36.7%) and A. oryzae (35.9%) whereas A. nidulans and A. terreus preferred tri-nucleotide SSRs (38.2 and 42.1%) in whole genome sequences. In transcripts, tri-nucleotide SSRs were the most abundant whereas di-nucleotide SSRs were the least favored. Motif conservation study among the transcripts revealed conservation of only 27% motif within Aspergillus species. Furthermore, a similar relationship among the Ascomycetes was obtained on the basis of motif conservation and conserved genes (rDNA). To analyze the diversity present within the Indian isolates of Aspergillus, primers were successfully designed for 692 motifs in A. niger and A. terreus of which 20 were selected for diversity analysis. Among all the markers amplified, 10 markers (83.3%) were polymorphic, whereas remaining two markers (16.6%) were monomorphic. Ten polymorphic markers acquired in this investigation showed the utility of recently created SSR markers in the assessment of genetic diversity among various isolates of Aspergillus.